PENERAPAN METODE BERCERITA UNTUK MENGEMBANGKAN MORAL PESERTA DIDIK - Andi Sumrah AP; Hamdayani Ilyas (LPPM Universitas Muhammadiyah Bulukumba, 2021)
This research is classroom action research. This study aims to describe the application of the storytelling method in developing the character and morals of students in PAUD. The research method applied consisted of two cycles, each cycle carried out in four stages, namely: planning, implementation, observation or evaluation, and reflection. The research was conducted at the Kuncup Mekar Permai Ela-Ela Kindergarten, Bulukumba Regency. The research subjects consisted of 17 students. The research was carried out in the 2019/2020 school year. The data used are test and non-test. The test technique was carried out with a written test at the end of each cycle. The non-test technique is carried out through observing student activities, student attitudes in each cycle, and documentation of learning activities. The application of the storytelling method using picture media as a learning method in teaching and learning activities can develop the moral and religious values ​​of early childhood in the Kuncup Mekar Permai Ela-Ela Kindergarten, Ujung Bulu District, Bulukumba Regency. The results of the actions in the first cycle of the first meeting were only 38 percent, and the first cycle of the second meeting increased to 46 percent. After the action was taken in the second cycle of meeting 1, the affective achievement standard of students increased to 65 percent, then further action was carried out in the second cycle of meeting 2 and again increased to 80 percent. Learners in the action process with the storytelling method reach the predetermined assessment standard, which is more than 75 percent.